(untitled) (Journal of the College of Basic Education, 2023)
He is Mustafa Sadiq bin Sheikh Abd al-Razzaq al-Rafi’i, the chief Sharia judge in Egypt, the grandson of Sheikh Abd al-Qadir al-Rafi’i, the head of the Rafi’i family whose lineage ends with the Rightly Guided Caliph Umar bin al-Khattab (may God be pleased with him).He was born in (Bahtim) on the first of Rajab 1298 AH, corresponding to the thirtieth of May 1881 AD, and grew up in the care of his father, and he was almost ten years old until he memorized the Holy Qur’an on it by memorization and recitation.He entered primary school in (Damanhour) and obtained his certificate in (Mansoura) when he was a few years old, and it is every plan of the certificates.He needed his father to learn from him, to understand narration and interpretation from him, to be aware of the best of the predecessors, to know the scholars of the nation, and to distance himself from the turmoil of life, after the disease distracted him from attending schools, as he left (typhoid) in his chest confining him and in his ear a sore, so he used to frequent walks and retreats among the lush fields in the (Tanta).He was appointed an employee in (Tanta) and ended up as a clerk in its (Sharia) court, and he spent forty years in his job.He composed poetry young, sent his poem and anthem in it, and brought out his collection in parts, some of which have not appeared to this day.